Dresta Sebagai Hukum yang Hidup dalam Penyelesaian Kehamilan di Luar Perkawinan di Desa Adat Tengkulung - Ni Wayan Kompiang Susilawati; Gede Mahardika; Ni Luh Gede Hadriani (Jayapangus Press, 2026)
Dresta is a living customary norm used to resolve social problems in Tengkulung Customary Village. However, its application in handling pregnancies outside marriage has not been documented, particularly regarding its basis, institutional procedures, and implications for affected parties. The purpose of this study is to analyze the forms and validity of dresta, its implementation process, and its implications for individuals, families, and the community’s socio-religious life. This study employed a descriptive-interpretive qualitative method. Fourteen informants were purposively selected from customary officials, Kertha Desa, youth, government, security personnel, religious figures, women and men previously involved, and their families. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed thematically and validated through source and method triangulation. The results show that the 2018 Awig-Awig of Tengkulung Customary Village does not explicitly regulate obligations for pregnancies outside marriage. Submitting one kilogram of rice and performing mecaru are recognized as dresta determined after clarification and a paruman decision. Termination of customary village membership is not automatic, but constitutes a final measure following repeated refusal to comply with a valid decision. The process includes confidential reporting, verification, examination, family mediation, paruman, determination of obligations, implementation, monitoring, and social reintegration. These findings confirm that dresta’s legitimacy depends on collective acceptance, institutional decisions, proportional obligations, and protection of affected parties. In conclusion, dresta clarifies responsibility and supports socio-religious recovery, but may produce stigma, gender-based pressure, and uncertainty when procedures are undocumented. Therefore, written guidelines, confidentiality, balanced responsibility, and protection for women and children are required.